DIAGNOSTICS OF RUNNING GEAR OF RAIL VEHICLES IN MOTION - Bohomaz, H. I.; Kovtun, Ye. M.; Markova, O. M.; Malyi, V. V.; Raznosilin, V. V. (Science and Transport Progress, 2004)
The possibility of estimating the technical state of railway vehicle running gears by their dynamic characteristics obtained during train motion with the help of developed diagnostic system is considered in the paper.